(untitled) (Tokyo, Japan, 1983)
This book was compiled for the purpose of introducing typical Japanese songs written in the style of European music who are interested in japan and japanese culture. The majority of these songs written for children, although some of them were composed for teenagers and adults. All of them are equally familiar to children, their parents and grandparents because they were taught in compulsory education courses.
Keywords: Children’s songs,Folk songs, Japanese,Songs, Japanese,Music; Intruction and study; Japan,Japan,Japan,Japan